2020
DOI: 10.1111/jpn.13312
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA sequencing of pectoral muscle tissue reveals microRNA‐mediated gene modulation in chicken muscle growth

Abstract: Sichuan mountainous black‐bone (SMB) chicken is a small‐sized black‐feathered chicken breed with low amount of meat, while Dahen (DH) chicken has a larger body size and a faster growth rate. MicroRNAs (miRNAs) are involved in various physiological processes, but their role in chicken muscle growth remains unclear. We aimed to investigate the miRNAs and pathways participating in the muscle growth of chicken. MiRNA profiles of four SMB chickens and four DH chickens were detected by small RNA sequencing. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Target prediction and network mapping suggests these miRNA may regulate calcium signaling, axonal guidance signaling, and NRF2-mediated oxidative stress response pathways ( Khatri et al., 2018 ). Profiling of the pectoral muscles of a small, slow-growing chicken breed (Sichuan mountainous black-bone) and a larger fast-growing chicken breed (Dahen) identified 32 differentially expressed miRNA between the 2 breeds at 10 wk of age ( Zhang et al., 2020 ). Target prediction analysis of these miRNA suggests they regulate fatty acid metabolism, immunity, and MAPK activation ( Zhang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target prediction and network mapping suggests these miRNA may regulate calcium signaling, axonal guidance signaling, and NRF2-mediated oxidative stress response pathways ( Khatri et al., 2018 ). Profiling of the pectoral muscles of a small, slow-growing chicken breed (Sichuan mountainous black-bone) and a larger fast-growing chicken breed (Dahen) identified 32 differentially expressed miRNA between the 2 breeds at 10 wk of age ( Zhang et al., 2020 ). Target prediction analysis of these miRNA suggests they regulate fatty acid metabolism, immunity, and MAPK activation ( Zhang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Profiling of the pectoral muscles of a small, slow-growing chicken breed (Sichuan mountainous black-bone) and a larger fast-growing chicken breed (Dahen) identified 32 differentially expressed miRNA between the 2 breeds at 10 wk of age ( Zhang et al., 2020 ). Target prediction analysis of these miRNA suggests they regulate fatty acid metabolism, immunity, and MAPK activation ( Zhang et al., 2020 ). At embryonic day 14, 5 miRNA were found to be differentially expressed in muscle between sex-linked dwarf chickens and normal chickens, and at 7 wk of age, 7 miRNA were differentially expressed ( Luo et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many QTLs linked to feed efficiency and its related traits have been deposited in the chicken QTL database ( (accessed on 8 July 2021). Although 882 precursor miRNAs, which generate 1232 mature miRNAs for Gallus gallus in the miRNA database miRBase (Release 22.1; (accessed on 10 August 2021), have been identified, limited numbers of miRNAs studies have been devoted to understanding the mechanism of feed efficiency [ 46 , 145 ] and related traits, such as growth [ 146 ] and skeletal muscle development [ 47 , 147 , 148 , 149 ], in chicken. In a genome-wide association study, Yuan et al [ 46 ] identified three significant SNPs for feed efficiency traits located in the vicinity of the miR-15a.…”
Section: The Mirnas Functions In Feed Efficiencymentioning
confidence: 99%
“…Both play a role in skeletal muscle growth and development [ 24 ]. Domestic chicken skeletal muscle studies are primarily concerned with the construct of the miRNA library and the function of specific miRNAs across breeds (high vs. low selection broilers [ 25 , 26 ] large vs. small broilers [ 27 ], broilers vs. laying hens [ 28 ]), developmental stages (embryonic [ 29 ], postnatal [ 30 , 31 ], embryonic to postnatal [ 8 ]), and skeletal muscle tissues (pectoral muscles, leg muscles). They are involved in a variety of biological processes related to skeletal muscle development and play a crucial role via a complex regulatory network.…”
Section: Mirna Modulates Skeletal Muscle In Domestic Chickenmentioning
confidence: 99%